Avsec Officer Service Excellent Analysis To The Security And Safety Of Aviation At The Security Check Point Of Tambolaka Airport In The New Normal Era. Study Program DIV Air Transportation Management, Bachelor level, Diploma IV Program, Yogyakarta College - Wilhelmina Florencia Koting; Rahimudin (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Avsec officers at the Tambolaka Airport Security Check Point are the front guard who meet and directly serve air transportation service users, but Avsec officers still lack awareness of appearance because they have not used uniforms and attributes according to the provisions. This study aims to determine the effect of Avsec officers excellent service on aviation security and safety and how much influence Avsec officers' excellent service has on flight security and safety at the Tambolaka Airport Security Check Point during the new normal period. Research using quantitative methods. Respondents' answers as primary data and data on the number of passengers in September as secondary data in the study. The population in this study were all users of air transportation services at Tambolaka Airport, while the research sample was determined from data on the number of passengers in September using the slovin formula. Data analysis performed included validity, reliability, and simple linear regression analysis The results of this study is influence of Avsec officers' excellent service on flight security and safety at the Tambolaka Airport Security Check Point during the new normal period. This is evidenced by the t-count 15.254 > t-table 1.985 and a significant value 0.00 <0.05. The results of this study also show the value of the coefficient of determination is 0.704. This value means that the great influence exerted by Avsec officers' excellent service on flight security and safety at the Tambolaka Airport Security Check Point during the new normal period was 70.4%.